Use of Adalimumab, a TNF-Alpha Inhibitor, is Associated with Paradoxical Psoriasis: Two Clinical Case Reports - Brugnera Nunes de Mattos, Alexandra; Maria Cerneski, Mariane; Reichert, Sheila; Nava Jaeger, Cassia (Brazilian Journal of Case Reports, 2023)
The use of tumor necrosis factor (anti-TNF) antagonists has become a practice applied in the treatment of various inflammatory diseases, such as psoriasis. However, the use of Anti-TNF can, paradoxically, trigger side effects as a form of psoriasiform or worsening of pre-existing symptoms, in patients with or without previously diagnosed psoriasis. In view of this, two case reports were described. First, we described a 21-year-old female patient who used adalimumab for four months due to extensive suppurative hidradenitis. In the second case, we related a 32-year-old male patient diagnosed with severe Crohn’s disease, with Adalimumab for three months developed psoriasis.